MATHEMATICS TEACHER'S PROFESSIONALISM IN TECHNOLOGY AND THE RELATIONSHIP TO THEIR TEACHING - Yulyanti Harisman; Muchamad Subali Noto; Mohd Hasril Amiruddin; Hamdani Syaputra; Suherman Suherman; Setiyani Setiyani (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
The background of this research is the importance of involving technology in the learning process. This study aims to see teachers’ interests, beliefs, and teaching processes using Adobe Premiere Pro software to categorize teachers’ professionalism. Furthermore, this study also describes the relationship between interests, beliefs, and the teaching process of teachers. This type of research is qualitative research with a case study method. 19 (nineteen) teachers from 11 (eleven) junior high schools in Padang, Indonesia were selected as research subjects. The research process has a reasonably long duration. At the beginning of the study, teachers were given the training to develop learning videos using Adobe Premiere Pro software. This software was chosen because it is challenging to use and is considered suitable as a medium for developing teacher digital literacy. The training was carried out in 5 meetings. The training is carried out by experts in their fields, from getting to know the tools to video rendering. Afterward, the teachers were given a questionnaire to determine their interest in the training. In addition, teachers are given open-ended questions to see teachers' beliefs in using technology in learning. The final stage of this research is to observe learning using observation sheets. This study found three types of teachers using technology: Technologically advanced teachers, technologically routine teachers, and technologically naive teachers. Technologically advanced teachers believe that technology plays an essential role in learning. Technologically routine teachers are teachers who sometimes use technology in the learning process, and technologically naive teachers are teachers who do not use technology in the learning process.